5500 ГэВ/нуклон энергитэй Pb+Pb үйлчлэлээр үүссэн саармаг бөөмсийг загварчлах - Ц, Баатар; Р, Тогоо; Б, Хүрэлбаатар (Scientific transaction of the National University of Mongolia. Physics, 2022)
The aim of high energy heavy ion physics is to study strong interacting matter at extreme energy densities. QCD predicts that, an sufficiently high energy density, there will be a phase transition from hadron matter to a plasma of deconfined quarks and gluons called a Quark-Glu Plasma(QGP). Such a phase transition would have taken place in the ea Universe some 10-5 seconds after the Big Bang and may still play a role in the core of collapsing neutron stars.